واقع مساهمة المؤسسات الصغيرة والمتوسطة في ترقية الصادرات خارج المحروقات في الجزائر - عبابسة، سمية; عياش ،زبير (University of Eloued جامعة الوادي, 2025)
لقد مرت الجزائر بالعديد من الأزمات باعتبارها دولة تعتمد على الاقتصاد الريعي بالدرجة الأولى، مما جعلها تعيد النظر وتبحث عن بدائل تمكنها من تنويع اقتصادها والخروج من التبعية للمحروقات ، وقد تفطنت الجزائر كغيرها من الدول إلى الدور الذي تلعبه المؤسسات المؤسسات الصغيرة والمتوسطة سواء عل الصعيد المحلي أو الدولي لدعم التنمية الاقتصادية والاجتماعية، حيث تبذل السلطات الجزائرية مجهودات لدعم وتشجيع المؤسسات الصغيرة والمتوسطة ومساعدتها على ولوج الأسواق الدولية وتنمية الصادرات خارج قطاع المحروقات، وقد حاولنا من خلال دراستنا التطرق لواقع المؤسسات الصغيرة والمتوسطة في الجزائر ومدى مساهمتها في ترقية الصادرات خارج قطاع المحروقات وقد خلصت هذه الدراسة إلى نتيجة مفادها أن تعداد هذا النوع من المؤسسات في الجزائر في تزايد مستمر، وأن مساهمتها في ترقية الصادرات متواضعة رغم المجهودات المبذولة في مرافقة المصدرين وتذليل عقبات العمليات التصديرية. Algeria has gone through many crises as a country that relies primarily on a rentier economy, which made it reconsider and look for alternatives that would enable it to diversify its economy and get out of dependence on hydrocarbons. Algeria, like other countries, has become aware of the role played by small and medium-sized enterprises, whether locally or internationally, to support economic and social development. The Algerian authorities are making efforts to support and encourage small and medium-sized enterprises and help them enter international markets and develop exports outsi the hydrocarbons sector. Through our study, we tried to address the reality of small and medium enterprises in Algeria and the extent of their contribution to promoting exports outside the hydrocarbon sector. This study concluded that the number of this type of enterprises in Algeria is constantly increasing, and that their contribution to promoting exports is modest despite the efforts made to accompany exporters and overcome obstacles to export operations.
The reality of the contribution of Small and medium entreprises in promoting exports outside hydrocarbons in Algeria
مقال
Keywords: المؤسسات الصغيرة والمتوسطة; ترقية الصادرات خارج المحروقات; small and medium entreprises; promotion of exports outside hydrocarbons